Evaluation of the Pintar Bersama Daihatsu (PBD) Program in Enhancing Students’ Hard Skills - Rohmad Munandar; Syarif Suhartadi; Eddy Sutadji (South Sulawesi Education Development (SSED), 2026)
The skills mismatch between vocational school graduates and industry demands remains a persistent issue in Indonesia, particularly in the automotive sector, where technological advancements require students to master increasingly complex competencies. This study evaluates the effectiveness of the Pintar Bersama Daihatsu (PBD) Program in enhancing the hard skills of students in the Light Vehicle Engineering (LVE/TKR) program at SMK Negeri 1 Sukorejo. Using a descriptive evaluative design with a qualitative approach, data were collected through observations, semi-structured interviews, questionnaires, and document analysis to assess program implementation, workshop practices, and competency outcomes. The findings reveal that the PBD Program significantly improved students’ technical abilities in diagnostics, periodic maintenance, and repair work, as evidenced by their increased proficiency in operating industry-standard tools and adhering to Daihatsu’s Standard Operating Procedures (SOPs). The structured hands-on training environment and instructor guidance played a crucial role in shaping these outcomes. However, several constraints were identified, including limited practice time, insufficient training vehicles, and high student-to-instructor ratios, which restricted opportunities for deeper skill mastery. Despite these challenges, the program effectively aligned school-based learning with industrial expectations and contributed to reducing the skills gap commonly observed among vocational graduates. The results underscore the importance of sustained school–industry collaboration, Teaching Factory–based learning, and investment in up-to-date workshop facilities to support vocational education reform. This study provides empirical evidence that manufacturer-standard workshop programs can serve as a viable model for enhancing technical competence and strengthening work readiness in the automotive vocational sector.